Assessing the Contribution of "the Bulan Bahasa Bali Festival" to Balinese Language Maintenance - Saputra, I Made Dian; Saputra, Aldi Dwi; Indriyo K. Sukmono, (Jurnal Kajian Bali (Journal of Bali Studies), 2026)
In response to concerns over the decline of regional languages, the Government of Bali Province has organized the Bulan Bahasa Bali Festival (Balinese Language Month Festival) annually since 2019 to revitalize the Balinese language and encourage its everyday use. This study assesses the festival’s contribution to language maintenance by examining participants’ perceptions, language practices, and the role of government policy. Employing a mixed-methods sequential explanatory design, data were collected from 180 participants across Bali through questionnaires, interviews, and observations. Quantitative findings indicate strong awareness and positive attitudes toward the Balinese language, while qualitative findings reveal that language use remains largely situational and concentrated during the festival period. These findings suggest a disparity between positive perceptions and sustained everyday language use. The study posits that the festival serves as an important policy instrument for language maintenance, although its impact on daily linguistic practices remains limited.
Keywords: Balinese Language; Bulan Bahasa Bali Festival; government language policy; language maintenance